2020
DOI: 10.1097/md.0000000000022965
|View full text |Cite
|
Sign up to set email alerts
|

Continuous epileptic negative myoclonus as the first seizure type in atypical benign epilepsy with centrotemporal spikes

Abstract: To figure out which diagnosis is more suitable and which antiepileptic drugs are more sensitive to epileptic negative myoclonus (ENM) as the first seizure type in atypical benign epilepsy with centrotemporal spikes. We reviewed the electroencephalogram (EEG) database of Linyi People's Hospital Affiliated to Shandong University and medical records of patients with ENM onset. The characteristics of epileptic seizures, onset age, treatment process, growth and development history, past disease history, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Data show that 20% of children with epilepsy may eventually have refractory epilepsy [ 3 ]. Long-term seizures of epilepsy may not only lead to persistent neuropsychiatric disorders, affect the cognitive function of children, but also adversely affect the growth and development of children [ 4 ]. The current clinical treatment methods mainly rely on oral antiepileptic drugs, vagus nerve stimulation, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Data show that 20% of children with epilepsy may eventually have refractory epilepsy [ 3 ]. Long-term seizures of epilepsy may not only lead to persistent neuropsychiatric disorders, affect the cognitive function of children, but also adversely affect the growth and development of children [ 4 ]. The current clinical treatment methods mainly rely on oral antiepileptic drugs, vagus nerve stimulation, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The falls were witnessed in both episodes, and no previous seizure-like activity, stroke, or LOC was witnessed prior to the fall. At the time, her therapeutic levels were above the desired therapeutic range of 250 - 550ng/mL [ 11 ] (older studies suggest up to 1000ng/mL [ 12 ]) as shown in Table 1 . However, in cases of refractory schizophrenia, a range above 350ng/mL may be the most optimal for an adequate response.…”
Section: Discussionmentioning
confidence: 99%
“…When cortical myoclonus arises in a sudden and paroxysmal manner, it is commonly termed, “partial epilepsy with motor symptomatology.” Nevertheless, the basic movement disorder phenotype is classified as focal myoclonus, either occurring as paroxysms of repetitive focal jerks, or as epilepsia partialis continua when occurring for long periods. Negative myoclonus can also occur ( Yang et al, 2020 ). There are various ictal EEG discharges that can be seen in the appropriate contralateral motor area during a focal motor seizure.…”
Section: Myoclonusmentioning
confidence: 99%